Two-point discrimination and judgment of laterality in individuals with chronic unilateral non-traumatic shoulder pain. (December 2021) - Caseiro, Marília; Reis, Felipe José Jandre dos; Barbosa, Amanda Matias; Barbero, Marco; Falla, Deborah; Oliveira, Anamaria Siriani de
Abstract: Background: Cortical representation of the painful body region may be disrupted in several chronic pain conditions. The two-point discrimination test (TPDT) and the Left/Right Judgement Task (LRJT) have been used to identify changes in the cortical body schema in several chronic pain conditions. However, it is unclear if these changes are present for all chronic pain mechanisms. Objectives: To investigate the integrity of the body schema of the painful shoulder in patients with chronic unilateral nociceptive shoulder pain. Methods: The sample consisted of 52 individuals with chronic unilateral nociceptive shoulder pain. The TPDT was measured over the anterosuperior and lateral regions of both shoulders using a staircase method. Participants also performed judgment tests of shoulder and foot laterality. The comparison of the TPDT and LRJT was performed using the linear regression model with mixed effects. Results: There was no difference in TPDT in the anterosuperior and lateral regions when comparing the symptomatic and asymptomatic shoulders. There was no difference in the LRJT accuracy and response time between the symptomatic and asymptomatic shoulders. No differences were observed when comparing LRJT variables from symptomatic shoulder and foot. Conclusion: Therefore, results do not provide clear evidence of altered body schema in chronic nociceptive unilateral shoulder pain. This suggest that alterations in body representations may depend on the primary pain mechanism. Highlights: TPDT and LRJT were used to explore possible alterations of the body schema in patients with chronic shoulder pain. No differences in TPDT and LRJT accuracy and response time were found. The spread of painful area was not associated with TPDT and left/right judgment ability. No clear evidence of disrupted body schema was found in chronic nociceptive unilateral shoulder pain.